Reuse and Biocompatibility of Hemodialysis Membranes: Clinically Relevant?. Issue 2 (8th January 2017) - Upadhyay, Ashish; Jaber, Bertrand L.
Abstract: The practice of reprocessing dialyzers for reuse, once predominant in the United States, has been steadily declining over the last 20 years. The professed roles of reuse in improving dialyzer membrane biocompatibility and lowering the risk of first‐use syndrome have lost relevance with the advent of biocompatible dialyzer membranes and favorable sterilization techniques. The potential for cost‐savings from reuse is also called into question by the easy availability of comparatively cheaper dialyzers and rising regulatory demands and operational cost of reprocessing systems. While the environmental concerns from additional dialyzer‐related solid waste from rising single‐use practice remains pertinent and requires development of safer dialyzer disposable system technologies, there is no meaningful medical rationale for the continued practice of dialyzer reuse in the twenty‐first century.